Confirmatory Factor Analysis of a Portuguese Version of the Pittsburgh Sleep Quality Index - C. M. Teixeira; A. Caçador; T. M. Ferreira; José Vasconcelos-Raposo (PsychTech & Health Journal)
The purpose of the present study is to determine the reliability and factorial validity of a Portuguese version of the Pittsburgh Sleep Quality Index - PSQI (Buysse, Reynolds III, Monk, Berman, & Kupfer, 1989). Methods: A random sample of 252 children (113 girls; 139 boys) attending the secondary school, with an average age of 15.27 years (SD = 1.925) that completed the Portuguese PSQI (P-PSQI). The factor structure of the data was evaluated using confirmatory factor analysis. Results: Once the “use of sleep medication” component was removed from the model a good overall fit to the data was found (χ2/df = 1.194, GFI = .983, AGFI = .959, CFI = .980, RMSEA = .029 [.001- .076] AICsat = 42.0). These results confirm the theoretical strength of PSQI; however, we were unable to confirm the seven-factor structure proposed in the original version. Conclusions: The PSQI-P has good psychometric properties and is suitable for use in nomothetic research on sleep quality in Portuguese adolescents.